Usefulness of early vascular phase images from contrast‐enhanced ultrasonography using Sonazoid for the diagnosis of hypovascular hepatocellular carcinoma. Issue 6 (22nd September 2015) - Hayashi, Hideki; Nishigaki, Yoichi; Tomita, Eiichi; Watanabe, Chiaki; Watanabe, Satoshi; Watanabe, Naoki; Suzuki, Yusuke; Kato, Tomohiro; Naiki, Takafumi
Abstract : Aim: This study aimed to evaluate the usefulness of early vascular phase images produced by contrast‐enhanced ultrasonography (CE‐US) with Sonazoid for the diagnosis of hypovascular hepatocellular carcinoma (HCC). Methods: Four hundred and seventeen patients with 674 hepatic nodules were evaluated using CE‐US with Sonazoid between January 2007 and March 2010. Retrospective analysis was conducted on 49 histologically confirmed nodules showing hypovascularity relative to the surrounding liver tissue in the early vascular phase and no enhancement defect in the Kupffer phase of CE‐US with Sonazoid. These nodules were classified according to early vascular phase image enhancement patterns as types I (largest avascular; avascular as a whole), II (second avascular; partially avascular), III (smallest avascular; not avascular, but faintly hypovascular relative to the surrounding liver) and IV (hypovascular as a whole with vessel‐like structures passing inside nodules). Results: Among the 49 nodules, types I, II, III and IV were identified in 19 (38.8%), nine (18.4%), 15 (30.6%) and six (12.2%) cases, respectively. The proportion of tumorous nodules (well‐differentiated HCC and high‐grade dysplastic nodules) significantly decreased with a reduction of the avascular area (68.4% in the type I, 55.6% in the type II and 33.3% in the type III nodules; P  < 0.05). All nodules demonstrating the type IV enhancement pattern were non‐tumorous. Conclusion: Based on the size of avascular area in the early vascular phase of CE‐US with Sonazoid, we can predict the malignant potential of the nodules. CE‐US with Sonazoid is very useful for evaluation of hypovascular hepatic nodules.